Enemy Beyond the Wall: Clinicopathological Features of Intrathyroidal Papillary Thyroid Carcinoma (T1-T3a) That Metastasize to Lymph Nodes Without Extrathyroidal Extension. (28th May 2021) - Tam, Abbas Ali; Ince, Nurcan; Baser, Husniye; Altinboga, Ayşegul Aksoy; Kilic, Mehmet; Topaloglu, Oya; Ozdemir, Didem; Alkan, Afra; Ersoy, Reyhan; Cakir, Bekir
Abstract: The aim of this study was to determine the clinicopathological features of papillary thyroid carcinomas (PTC) without extrathyroidal extension (ETE) and with lymph node metastasis (LNM). PTC > 1 cm increased the risk of LNM by 2.161 times compared to papillary thyroid microcarcinoma. The risk increased by 3.774 times in males and 1.553 times in the presence of multifocality. Presence of vascular invasion (VI) increased the risk of LNM by 3.093 times in patients without capsular invasion (CI). Clinicians should be careful about possible LNM in patients with large primary tumor diameter, multifocal tumors, CI and VI.